Drive thru history with Dave Stotts. Asia Minor: East Meets West - Stotts, Dave. ([United States] : Tyndale Entertainment, 2006)
This isn't your typical tour of ruins and dusty artifacts. It's history as exciting today as it was 2000 years ago! In a style all his own, Dave Stotts speeds through the world of ancient Asia Minor, giving you a fast-paced encounter with the people, places and events that have shaped our world and the Christian faith. His adventures include on-location explorations, loads of animations and narration that's definitely "outside the classroom." You may never read the Bible the same way again!
Episode 1 (31:32): The fairy chimneys of Cappadocia, Hittites and King David, Shopping in the bazaar, The underground cities. -- Episode 2 (36:22): Istanbul's history, Emperor Constantine's conversion. Edict of Milan. Nicene Creed. Fall of Constantinople, Hagia Sofia. -- Eposode 3 (38:14): Best of drive thru history. Bloopers. Western civilization comes to America.
"Focus on the family"--Container.
No publisher's number.
Includes bonus material.
Host, Dave Stotts.
Closed-captioned.
Keywords: Christian education -- History -- Early church, ca. 30-600.; East and West -- Antiquities; East and West -- Description and travel; Turkey -- Antiquities; Turkey -- Description and travel